The God who neither is nor is not : a theological evaluation of Richard Kearney’s “God who may be” - Veldsman, Daniel Petrus (University of Pretoria, 2018)
Dissertation (MTh (Dogmatics and Christian Ethics))--University of Pretoria, 2012.